Channels for the impact of the war in Ukraine on the commercial banking sector in Poland: First results of the study - Michał Bernardelli; Zbigniew Korzeb; Pawel Niedziółka; Krzysztof Waliszewski (Contemporary Economics, 2023)
The outbreak of war in Ukraine raises questions about its impact on the economies and financial systems of countries directly and indirectly involved in the war, but also on the economies of non-participating countries. The article aims to identify the channels through which the war in Ukraine has affected commercial banking in Poland. The original contribution of this paper to the literature dedicated to the impact of the outbreak of war on financial sector consists in the identification of channels of direct and indirect effects of war on commercial bank performance, adoption of unique empirical strategy to point out features of banks determining their sensitivity to the materialisation of geopolitical risk as well as groups of banks whose shares move along similar trajectories during the war. The conclusions emphasize that the long-term negative indirect effects of the war outweigh the short-term indirect ones. The policy implications consist in the benefits of introduction of new reporting standards for banks that focus on the exposure of their clients to the geopolitical risk, augmentation of scope of risks to be covered by regulatory capital by geopolitical risk as well as creation scenarios of stress tests that would include geopolitical risk. Facing war, the implications for commercial banks' managers come down to the necessity to prioritize cyber risk management and implement a new paradigm of credit and market risk assessment, taking into account the impact of geopolitical factors.
Keywords: G21; 330; banking sector; banking crisis; war; credit portfolio; capital market; liquidity